The Reality And Future Of The Political System In Russia In Light Of The War On Ukraine - نبيل علي; محمد السعدي (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Russia inherited the status of the Soviet Union legally, but without possessing any of the factors of political power that the Soviet Union enjoyed, so the political system in Russia appeared in the period 1991-1999 as a weak regime that followed American and Western policies, exhausted in dealing with the issues of economic transformation and the deterioration of the situation. annuity. This situation remained the same until Russian President Vladimir Putin came to power in the year 2000, who began developing a plan based on a new strategic direction, based on reproducing a strong state internally and externally, and working vigorously to change the working mechanisms of Russian international relations, and reshaping them in the way that It enjoys acceptance and support, and building international relations based on cooperation and competition, not conflict and war. The change in the internal strategic environment in Putin’s time, the change in the nature of perceptions that govern Russia, and the work to find a successful alternative to the factors of military power with economic power formed important factors in the reproduction of a strong Russia, supported with a political system that has well proven its ability to shape the features of that country. Those ideal conditions created a state of balance in the relationship with the West, which the United States of America was not satisfied with, so it pushed for imposing a state of tension in the relationship with Russia, by imposing its influence in Russia’s immediate regional neighbors, including Ukraine, which Russia considered a direct threat to its national security. Thus, the Russian presidential institution began to re-orient its strategic direction in a way that serves its national security first, and takes into account its economic interests second.